Sarcocystis species identification in the moose (Alces alces) from the Baltic States - Prakas, Petras; Kirillova, Viktorija; Calero-Bernal, Rafael; Kirjušina, Muza; Rudaitytė-Lukošienė, Eglė; Habela, Miguel Ángel; Gavarāne, Inese; Butkauskas, Dalius (Parasitology Research, 2019)
Various muscle tissue samples from 60 moose (Alces alces) in the Baltic region were examined for Sarcocystis species. Sarcocysts were detected in 49 out of 60 (81.7%) moose investigated. Six species, Sarcocystis alces, Sarcocystis hjorti, Sarcocystis linearis, Sarcocystis silva, Sarcocystis ovalis, and Sarcocystis sp., were identified using light microscopy (LM), and DNA sequence analysis (cox1 and 18S rDNA). Sarcocysts of S. alces, S. ovalis, and S. hjorti were studied using transmission electron microscopy (TEM); sarcocyst walls of S. alces, S. ovalis, and S. hjorti were type 25, type 24, and type 7a, respectively. Sarcocystis linearis previously found in roe deer and red deer was also shown to use moose as an intermediate host for the first time. The unknown Sarcocystis sp. was rare and might employ another main intermediate host. Phylogenetic results demonstrated that Sarcocystis sp. was most closely related to Sarcocystis tarandivulpes, using canids as definitive hosts.